Artificial water points facilitate the spread of an invasive vertebrate in arid Australia. Issue 3 (21st March 2014) - Letnic, Mike; Webb, Jonathan K.; Jessop, Tim S.; Florance, Daniel; Dempster, Tim; Rhodes, Jonathan
Summary The spread of invasive species after their initial introduction is often facilitated by human actions. In some cases, invaders only become established in habitats where dominant native species have been displaced as a result of human actions or where humans inadvertently provide essential resources such as food, water or shelter. We investigated if dams that provide water for livestock have facilitated the cane toad's (Rhinella marina) invasion of a hot semi‐arid landscape by providing toads with a resource subsidy and hence refuge from extreme heat and aridity. To determine the relationship between the presence of surface water and habitat occupancy by toads, we surveyed natural and artificial water features for cane toads during the annual dry season. We used radiotracking and acoustic tags to determine whether movement patterns and shelter use of cane toads were focussed around dams. To determine whether dams provide toads with refuge from extreme heat and aridity, we deployed plaster models with internal thermometers to estimate ambient temperatures and toad desiccation rates in shelter sites. To determine whether dams alleviate the stress experienced by toads, we measured plasma corticosterone levels of toads that sheltered in and away from dams. Toads were present in sites with standing water and absent from waterless sites. Most radiotracked toads sheltered within 1 m of water. Toad movements were focussed around water. Toads tracked with passive acoustic telemetry over a 6‐month dry season were highly resident at dams. Plaster models placed in toad shelter sites away from the water lost 27% more mass and experienced higher temperatures than models placed near the water's edge. Toads that sheltered in terrestrial shelters exhibited higher plasma corticosterone levels compared to toads that sheltered near dams. Dams provide toads with refuge habitats where they are less at risk from overheating and dehydration. Synthesis and applications. Artificial water points can facilitate biological invasions in arid regions by providing a resource subsidy for water‐dependent invasive species. Our study suggests that there is scope to control populations of water‐dependent invasive vertebrates in arid regions by restricting their access to artificial water points.